ARCube—The Augmented Reality Cube for Archaeology. (22nd August 2014) - Jiménez Fernández‐Palacios, B.; Nex, F.; Rizzi, A.; Remondino, F.
Abstract : Augmented Reality (AR) allows the direct and intuitive access of digital objects visualized in real time on computer screens. AR applications are commonly used in many different areas, such as entertainment, sports and tourism, while their use in archaeology is still limited. When employed, current archaeological AR applications use expensive devices or flat targets, which are insufficient for visualizing complex artefacts. In this paper, we present a low‐cost, automated method called the ARCube System, which allows the expansion and enrichment of AR applications focused on archaeological objects. In this paper, the newly developed ARCube System is described by presenting several archaeological examples to show the system's ability to visualize and investigate archaeological finds. The reported tests demonstrate the method's reliability on a variety of objects characterized by different shapes and sizes. The ARCube System allows users to interact with digital 3D models, rotate them through 360° and explore details in high resolution (without any risk of damaging the find). The system renders 1:1 scale between digital and actual object and offers a low‐cost flexible system for the interactive visualization of archaeological finds that can be beneficial to public research (e.g., museum exhibits) and education (e.g., the classroom) and may possibly lead to new avenues of archaeological research.